Ethics and Law in Clinical Practice: Public Health - Wijaya, Hanna; Firmansyah, Yohanes; Sylvana, Yana; S., Michelle Angelika; Utomo, St. Laksanto (International Journal Labs, 2022)
Background: Public health is the study of disease prevention to enhance individuals' quality of life. Since the 14th century, public health research has grown in Indonesia. Aim: This research aimed to discuss issues on the health sector, with the primary area of debate being law. Method: This research employs a systematic review of the literature, which belongs to qualitative approach, that is organized by subject and then thoroughly assessed. Findings: Public health services are designed to help people improve their health and reduce the risks of exercising their right to health. A multicultural society is today's public-health concern.